Lung injury associated with severe Epstein-Barr virus (EBV) infection - Cui, Yun (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2015)
OBJECTIVE: Severe Epstein-Barr (EB) virus infection is potentially a devastating process that often leads to death encountered in pediatrics recently. Inappropriate control of EB virus replication may cause severe infection resulting in multiple organ dysfunction. However, little information is available on pulmonary complications associated with EB virus infection. The aim of the present study was to investigate severe EB virus (EBV) infection complicated with lung injury in pediatric intensive care unit (PICU), including clinical characteristics, laboratory or imaging feature and outcomes